2018
DOI: 10.1002/pon.4931
|View full text |Cite
|
Sign up to set email alerts
|

Applying the theory of planned behavior to examine adjuvant endocrine therapy adherence intentions

Abstract: Objective Adherence to adjuvant endocrine therapy (AET) in breast cancer survivors is suboptimal. Using the theory of planned behavior (TPB), this study aimed to identify the strongest predictors from the TPB of AET intentions and past behavior and assessed whether ambivalence and anticipatory emotions increased the predictive capacity of TPB. Methods Two hundred eighty women diagnosed with hormone positive (HR+) breast cancer who filled at least one prescription of AET responded to a survey measuring TPB cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
3
19
0
Order By: Relevance
“…The findings of the present study showed that interventions based on the theory of planned behavior can be effective in creating safe behavior of supervisors. The findings of the present study are consistent with other studies that show the effectiveness of the theory of planned behavior in nutritional behavior,[ 18 ] energy savings in the workplace,[ 19 ] use of appropriate vehicles to reduce air pollution,[ 20 ] following the treatment,[ 21 ] infant nutrition,[ 22 ] and physical activity. [ 23 ]…”
Section: Discussionsupporting
confidence: 90%
“…The findings of the present study showed that interventions based on the theory of planned behavior can be effective in creating safe behavior of supervisors. The findings of the present study are consistent with other studies that show the effectiveness of the theory of planned behavior in nutritional behavior,[ 18 ] energy savings in the workplace,[ 19 ] use of appropriate vehicles to reduce air pollution,[ 20 ] following the treatment,[ 21 ] infant nutrition,[ 22 ] and physical activity. [ 23 ]…”
Section: Discussionsupporting
confidence: 90%
“…Thus, mapping our findings onto the Theory of Planned Behavior (TPB) contributes to advancing novel, tailored family interventions promoting cancer predisposition cascade genetic testing for BRCA . This theoretical contribution towards developing complex interventions promoting cascade screening is further supported by the demonstrated utility of the TPB in breast cancer and genetic counseling [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 97%
“…Accordingly, the United Kingdom Medical Research Council recommends integrating relevant theories/frameworks when developing complex interventions [ 23 ]. One theory, the Theory of Planned Behavior (TPB) [ 24 ], has been effectively used in the context of breast cancer to describe a wide range of cancer-related behaviors including screening/mammography [ 25 ], risk-reducing surgeries [ 26 , 27 ], lymphedema risk reduction activities [ 28 ], adherence to adjuvant endocrine therapies [ 29 ], as well as contacting potentially at-risk relatives [ 30 ]. Similarly, the TPB has been employed in the field of genetic counseling [ 31 ] to better understand and predict behaviors around prenatal genetic testing [ 32 ] and expanded carrier screening [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Following these previous applications, we recommend extending these applications to a broader variety of desirable but difficult behaviors. For instance, recent research investigating adherence to adjuvant endocrine therapy (AET) in breast cancer survivors has shown that women who associate positive emotions, such as calm and hopeful, with treatment (both positive emotions are associated with an abstract mindset) reported higher intentions of adherence (Hurtado-de-Mendoza et al, 2019). These results highlight the necessity of tailoring health promotion campaigns to focus on positive emotions and considering that women may have to endure the side effects of AET in the short term for greater chances of survival in the long term (a large personal challenge).…”
Section: Discussionmentioning
confidence: 99%